Learning Organization Practices And Organizational Effectiveness: The Impact Of Type Of Company - Reginald See, Theam Kwooi (2002)
The immense changes in the economic environment caused by globalization and technology have forced organizations to make significant transformations in order to adapt and survive i this new world. Without continual learning, new innovations in terms of products and services will not be possible; hence, organization will not remain profitable. So, it has become important that an organization learns, adapts and changes with the environmental conditions to become an effective learning organization that lead to organizational effectiveness in the 21 st century.